Platelet response following dexamethasone in obese vs nonobese patients with primary, acute immune-mediated thrombocytopenia - Tyler Everhardt; Kelley Julian; Russell Benefield; Aaron Wilson; Nathan Wilson; Charles J. Parker; Anna Parks; Jeffrey A. Gilreath (Research and Practice in Thrombosis and Haemostasis)
Background: Immune thrombocytopenia (ITP) is a rare autoimmune disorder defined as a platelet count <100,000/μL, where secondary causes of thrombocytopenia have been excluded. Glucocorticoids are firstline therapy for ITP; however, data and recommendations on the impact of body weight and repeat steroid courses remain limited. Objectives: We aimed to evaluate if body weight altered the response rates to dexamethasone (DEX) in the treatment of ITP. Methods: We conducted a retrospective review to evaluate the effects of body weight on response to DEX in ITP. Patients were compared based on body mass index, presentation of ITP (acute or chronic), and cause of ITP (primary or secondary). Initial response, complete response, and relapse rates were among the outcomes investigated among the primary acute ITP population. Results: Overall, 117 patients with ITP were identified, 49 of whom had primary acute ITP. Of these, 28 were categorized as nonobese, while 21 were obese. Nonobese patients were more likely to experience an initial platelet response to DEX than obese patients (93% vs 71%; P = .04), with 68% of nonobese patients also demonstrating a complete response compared with 48% of obese patients. Among patients who did not respond after 1 course of DEX, only 2 patients received another course prior to the initiation of alternative therapies. This is the second study to show that obese patients with primary acute ITP have significantly lower initial response rates and lower complete response rates to DEX compared with nonobese patients and that repeat DEX courses may be underutilized across all body mass index subgroups. Conclusion: This study further highlights the need for additional data and guidance on optimal glucocorticoid dosing, especially in patients with obesity.